A comparative finite elemental analysis of glass abutment supported and unsupported cantilever fixed partial denture. Issue 5 (May 2015) - Ramakrishaniah, Ravikumar; Al kheraif, Abdulaziz A.; Elsharawy, Mohamed A.; Alsaleh, Ayman K.; Ismail Mohamed, Karem M.; Rehman, Ihtesham Ur
Abstract Objective The purpose of this study was to investigate and compare the load distribution and displacement of cantilever prostheses with and without glass abutment by three dimensional finite element analysis. Micro-computed tomography was used to study the relationship between the glass abutment and the ridge. Methods The external surface of the maxilla was scanned, and a simplified finite element model was constructed. The ZX-27 glass abutment and the maxillary first and second premolars were created and modified. The solid model of the three-unit cantilever fixed partial denture was scanned, and the fitting surface was modified with reference to the created abutments using the 3D CAD system. The finite element analysis was completed in ANSYS. The fit and total gap volume between the glass abutment and dental model were determined by Skyscan 1173 high-energy spiral micro-CT scan. Results The results of the finite element analysis in this study showed that the cantilever prosthesis supported by the glass abutment demonstrated significantly less stress on the terminal abutment and overall deformation of the prosthesis under vertical and oblique load. Micro-computed tomography determined a gap volume of 6.74162 mm3. Significance By contacting the mucosa, glass abutments transfer some amount of masticatory load to the residual alveolar ridge, thereby preventing damage to the periodontal microstructures of the terminal abutment. The passive contact of the glass abutment with the mucosa not only preserves the health of the mucosa covering the ridge but also permits easy cleaning. It is possible to increase the success rate of cantilever FPDs by supporting the cantilevered pontic with glass abutments.